2024
DOI: 10.1111/sed.13161
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon ages of microcrystalline authigenic carbonate in Lake Neusiedl (Austria) suggest millennial‐scale growth of Mg‐calcite and protodolomite

Stephanie Neuhuber,
Susanne Gier,
Erich Draganits
et al.

Abstract: Authigenic Mg‐calcite and dolomite are frequently observed in restricted, evaporative environments, such as lagoon or lake systems, but their formation is difficult to capture due to slow growth rates. Lake Neusiedl, an alkaline and subhaline lake with a mean water depth of 0.7 m in Austria, offers a natural system to study the precipitation of Ca‐Mg‐carbonate phases, which occur as fine‐grained, unconsolidated and largely homogenized mud. To elucidate the timing and formation mechanisms of these authigenic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…After accounting for the minimal <1 wt.% detrital Precambrian dolomite (Peterson et al ., 1963; Clayton & Jones, 1968), the carbonate sedimentation rate for Deep Springs Lake is approximately 0.01 to 0.50 mm/year. Recent radiocarbon work has shown that Lake Neusiedl has a carbonate sedimentation rate that ranges from 0.08 to 0.30 mm/year (Neuhuber et al ., 2023). Holocene carbonate sedimentation rates have been reported in literature to be 0.30 to 3.00 mm/year in Florida Bay, the Bahamas and Bermuda (Strasser & Samankassou, 2003), 0.29 mm/year off the coast of Abu Dhabi (Lokier & Steuber, 2009), 0 to 1.20 mm/year in northern Belize (Yang et al ., 2004) and 0.16 mm/year in stromatolites from San Salvador, Bahamas (Paull et al ., 1992).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After accounting for the minimal <1 wt.% detrital Precambrian dolomite (Peterson et al ., 1963; Clayton & Jones, 1968), the carbonate sedimentation rate for Deep Springs Lake is approximately 0.01 to 0.50 mm/year. Recent radiocarbon work has shown that Lake Neusiedl has a carbonate sedimentation rate that ranges from 0.08 to 0.30 mm/year (Neuhuber et al ., 2023). Holocene carbonate sedimentation rates have been reported in literature to be 0.30 to 3.00 mm/year in Florida Bay, the Bahamas and Bermuda (Strasser & Samankassou, 2003), 0.29 mm/year off the coast of Abu Dhabi (Lokier & Steuber, 2009), 0 to 1.20 mm/year in northern Belize (Yang et al ., 2004) and 0.16 mm/year in stromatolites from San Salvador, Bahamas (Paull et al ., 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Newly precipitated dolomite nanocrystals formed through epitaxial growth as they follow crystallographic orientations of bulk crystals demonstrated by SAED and TEM images (Figs 6, 10 and S12). Similar nucleation and growth of nanocrystal dolomites is also observed in modern sediments such as the Great Salt Lake with dissolved silica as a catalyst (Fang et al ., 2023a), Lake Neusiedl (Meister et al ., 2023; Neuhuber et al ., 2023), the Coorong region (Raudsepp et al ., 2022) and Abu Dhabi sabkha (Wenk et al ., 1993), as well as in older rock such as Dolomia Principale (Meister & Frisia, 2019), dolomite crust associated with deep sea modern methane seeps (Xu, 2010) and the eastern Dolomites, Northern Italy (Preto et al ., 2015). The small misoriented nanocrystals of dolomite indicate that they formed directly and nucleated on bulk crystals implying a primary precipitation origin as opposed to replacement products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations